Design of wearable device to assist cerebral palsy children in standing and walking - Mahamud F.; Anuar A. (Penerbit UTM Press, 2023)
Most children with cerebral palsy (CP) have difficulties in standing and walking. They would normally require assistive device to help in standing and walking. This paper describes the process that was carried out to design a wearable brace for the lower limb. This brace is intended to provide support during standing and walking for ambulant CP children. Design requirements were drawn up by conducting surveys and interviews with parents, CP child caregivers, and CP children. Safety is very crucial for the device, where special care is made to ensure it would not pose any hazard to the children and also the caregivers. Based on these information and the anthropometric measurements, the device has been designed and analyzed using 3D CAD software. From the analysis, the device shown to function as expected. 2015, Penerbit UTM Press. All rights reserved.